Sources Identification of Nitrogen Using Major Ions and Isotopic Tracers in Shenyang, China - Huan Huang; Mingzhu Liu; Junjie Wang; Jiangtao He; Honghan Chen (Geofluids)
Stable isotopes are natural tracers that can provide quantitative information about the surface water/groundwater interactions and sources of pollutants in water. In this study, we measured δ18Owater and δ2Hwater and δ18Onitrate and δ15Nnitrate of the samples from the Hun River and groundwater in Shenyang City, China, where the water from the Hun River has a strong discharge and recharge connection with the groundwater. δ18Owater and δ2Hwater were used to determine the amount of surface water that was discharged into groundwater, while δ18Onitrate and δ15Nnitrate were employed to determine the sources of nitrate and ammonium in groundwater, which are the main contaminants in the study area. The reducing environment in groundwater may result from the prevailing iron and manganese, occurring from weathering of minerals and rocks, which prevents the ammonium being oxidized into nitrate. Results show that the amount of recharge from the Hun River into groundwater accounts for around 55.56–86.60% of the total groundwater in the dry season, and the ratio changed to 30.97–63.79% in the wet season. Multiproxy analysis (stable isotope analyses in combination with chemical and hydrogeological data of the study area) indicates that human activities, such as manure and sewage discharge, are the prevailing source of nitrogen in the waters.